Pengaruh Aktif Berorganisasi, Manajemen Waktu, dan Self Efficacy terhadap Prestasi Belajar Mahasiswa Fakultas Ekonomi Bisnis dan Pariwisata Universitas Hindu Indonesia Denpasar - Darmawan, Achmad Putra; Putri Trarintya, Mirah Ayu; Suputra, Gusti Alit (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
With various activities on campus, it is hoped that students can add insight and direct them to positive things, which in the end they can. optimizing student academic achievement. One of the indicators is the Grade Point Average (GPA). However, to obtain brilliant academic achievements requires maximum effort. This is what underlies the formulation of the problem and the purpose of this study, namely to determine the effect of active organization (X1), time management (X2), and self-efficacy (X3) on student achievement. The population for this study consisted of students from batch 2019 who had been active in organizations for more than two years at the Faculty of Economics, Business and Tourism, UNHI. The research sample consisted of 70 respondents who were selected in a proportionate stratified manner. Methods of data analysis include validity test, reliability test, classic assumption test, multiple linear regression, determining the coefficient of determination, as well as t test and F test. Based on the findings of this study, it is shown that partially active organization and self-efficacy have a significant positive effect on learning achievement, while time management has no effect on it. Simultaneously Active Organization, Time Management and Self Efficacy have a significant positive effect on Learning Achievement. The magnitude of the influence of independent variables on student achievement is 58.0%.Seeing the results of the research, in the future, apart from being active in organizations, students can also be active in participating in workshops related to their interests and talents which will make it easier for students to recognize their talents.